(untitled) (Journal of Educational Management, 2016)
The objective of this study was to survey the description of accounting teachers of the senior high school accounting curriculum. This involved the description of the formal documented accounting curriculum. This study was undertaken to gauge the level of quality implied in the implementation of the curriculum by ascertaining the accounting teachers’ fidelity of the interpretation of same. The study recruited 155 senior high school accounting teachers from senior high schools in the Northern, Brong Ahafo, and Western Regions of Ghana. These participants were surveyed by an Innovation Configuration Checklist (ICC). It was found in the study that the senior high school accounting teachers differed markedly in their description of the senior high school accounting curriculum. This was a departure from the evidence the curriculum provided. Accordingly, it was concluded that the fidelity of accounting teachers’ interpretation of the accounting curriculum and use of same was doubtful.